1995
DOI: 10.1210/mend.9.12.8614415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PML and PML-RAR on the transactivation properties and subcellular distribution of steroid hormone receptors.

Abstract: PML (promyelocytic leukemia) is a protein involved in the t (15;17) translocation of promyelocytic leukemia and is mainly localized in nuclear bodies. Here we show that PML exerts a very powerful enhancing activity (up to 20-fold) on the transactivating properties of the progesterone receptor (PR) and has a similar effect on several other steroid hormone receptors. There is probably a direct or indirect interaction between PR and PML, because when the latter was expressed at high concentrations it shifted PR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 54 publications
0
50
0
Order By: Relevance
“…This rearrangement is much more frequently observed as compared with other known APL fusionproteins, PLZF/RARa (Chen et al, 1993), NPM/ RARa (Redner et al, 1996) and NuMA-RARa (Wells et al, 1997) reported in M3 leukemias. In addition, PML possesses structural and functional features of a transcription factor (Kastner et al, 1992;Guiochon-Mantel et al, 1995), and biological activity of a growth regulator (Mu et al, 1994). PML mRNA and protein expression is low in quiescent HPCs and is induced by growth factor stimulation of Figure 6 E ect on BFU-E colony formation upon HPCs treatment with appropriate concentrations of (i) antisense (AS) oligomer to PML (a1-PML), (ii) antisense oligomer to Rb (a-Rb), (iii) scrambled a1-PML (Scr a1-PML) and/or (iv) scrambled a-Rb (Scr aRb), added alone or in combination as indicated at day 5 of culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rearrangement is much more frequently observed as compared with other known APL fusionproteins, PLZF/RARa (Chen et al, 1993), NPM/ RARa (Redner et al, 1996) and NuMA-RARa (Wells et al, 1997) reported in M3 leukemias. In addition, PML possesses structural and functional features of a transcription factor (Kastner et al, 1992;Guiochon-Mantel et al, 1995), and biological activity of a growth regulator (Mu et al, 1994). PML mRNA and protein expression is low in quiescent HPCs and is induced by growth factor stimulation of Figure 6 E ect on BFU-E colony formation upon HPCs treatment with appropriate concentrations of (i) antisense (AS) oligomer to PML (a1-PML), (ii) antisense oligomer to Rb (a-Rb), (iii) scrambled a1-PML (Scr a1-PML) and/or (iv) scrambled a-Rb (Scr aRb), added alone or in combination as indicated at day 5 of culture.…”
Section: Discussionmentioning
confidence: 99%
“…PML has been regarded as a growth regulator (Mu et al, 1994;Liu et al, 1995;He et al, 1997a;Guiochon-Mantel et al, 1995). Indeed, when overexpressed, it suppresses: (i) anchorage-independent growth of APL-derived NB4 cells (Mu et al, 1994); (ii) oncogenic transformation of rat embryonic ®broblasts by cooperative oncogenes and of NIH3T3 cells by activated Neu ; and (iii) growth and tumorigenicity of prostate cancer cells (He et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, PML NBs were shown to be disorganized during many viral infections. This link between PML bodies and the imunoproteasome could account for a number of apparently contradictory observations, such as the susceptibility of PML7/7 mice to infections or the frequent colocalisation of PML and overexpressed/misfolded proteins (Fabunmi et al, 2001;Guiochon-Mantel et al, 1995;Skinner et al, 1997;Wang et al, 1998a).…”
Section: Arsenic Targeting Of Pml: Implications For Apl Nb Formationmentioning
confidence: 99%
“…Both PML and PML-RARa were shown to potentiate the transactivating functions of AP-1 (Jun/Fos) (Doucas et al, 1993;Vallian et al, 1998b), the steroid receptors (Guiochon-Mantel et al, 1995), and the hematopoietic transcription factor GATA-2 (Tsuzuki et al, 2000). Further investigations have established that PML does not interact directly with either Jun/Fos or steroid receptors but instead targets transcriptional accessory factors such as CBP and nuclear receptor cofactor TIF1a (Doucas et al, 1999;Vallian et al, 1998b;Zhong et al, 1999).…”
Section: Pml Pods and Transcriptional Regulationmentioning
confidence: 99%